Comparative analysis of different chlorine-free extraction on oil palm mesocarp fiber - Pereira, Paulo Henrique F. [UNESP]; Souza, Nágila F.; Ornaghi, Heitor Luiz [UNESP]; de Freitas, Morsyleide Rosa (Elsevier, 2020)
Biobased products are a growing trend in industrial crops, but the natural variation among the plant sources demands the development of efficient pretreatments for standardizing the raw material. This work aims to evaluate the characteristics of pressed oil palm mesocarp fiber after alkaline and multi-step pretreatment methods. Multi-step pretreatment procedure involved acetosolv extraction with a mixture of 93 % (w/w) of acetic acid and 0.3 % (v/v) of hydrochloride acid (a chlorine-free), followed by alkaline bleaching. Acetosolv extraction was also used aiming to allow a more effective delignification during the bleaching stage, and the possibility to recover the solvent that was used in the next extractions; this fact could not be obtained in alkaline extraction alone. The fibers were evaluated concerning the chemical composition, X-ray diffraction, thermogravimetric analysis, scanning electron microscopy, and Fourier-transform infrared spectroscopy. The combined multi-step resulted in higher alpha-cellulose content (66 %), crystallinity index (65.20 %), and lower mass loss up to the onset degradation step.
Keywords: Chemical treatment; Chlorine-free extraction; Hydrogen peroxide treatment; Lignocellulosic fiber; Oil palm fibers